2013
DOI: 10.3855/jidc.2629
|View full text |Cite
|
Sign up to set email alerts
|

Enteric fever burden in North Jakarta, Indonesia: a prospective, community-based study

Abstract: Introduction: We undertook a prospective community-based study in North Jakarta, Indonesia, to determine the incidence, clinical characteristics, seasonality, etiologic agent, and antimicrobial susceptibility pattern of enteric fever. Methodology: Following a census, treatment centre-based surveillance for febrile illness was conducted for two-years. Clinical data and a blood culture were obtained from each patient. Results: In a population of 160,261, we detected 296 laboratory-confirmed enteric fever cases d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
5
15
0
Order By: Relevance
“…The Salmonella serovars found in this study were 55.4% S. Typhi and 44.6% S. Paratyphi A , which was in line with a study in Indonesia that showed the predominance of S. Typhi over S. Paratyphi [11]. Studies in India and China stated that the reason for increasing prevalence of S. Paratyphi A over S. Typhi in recent years was the increased use of Vi polysaccharide vaccine [12].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The Salmonella serovars found in this study were 55.4% S. Typhi and 44.6% S. Paratyphi A , which was in line with a study in Indonesia that showed the predominance of S. Typhi over S. Paratyphi [11]. Studies in India and China stated that the reason for increasing prevalence of S. Paratyphi A over S. Typhi in recent years was the increased use of Vi polysaccharide vaccine [12].…”
Section: Discussionsupporting
confidence: 88%
“…A study in Asian countries showed that resistance rates in Bangladesh were 39.5% for ciprofloxacin, 68.4% for ampicillin, 57.9% for trimethoprim, and 68.4% for sulfamethoxazole, in Vietnam 0.0% for ciprofloxacin, and 80.4% for ampicillin, trimethoprim, and sulfamethoxazole, while in Indonesia they were 0.0% for ciprofloxacin, 1.8% for ampicillin and trimethoprim, and 3.6% for sulfamethoxazole [17]. A community-based study from 2001 to 2003 in Indonesia showed low resistance rates of S. Typhi and S. Paratyphi, where only 2.5% isolates of S. Typhi were resistant against ampicillin, while there was no resistance against trimethoprim-sulfamethoxazole, ceftriaxone, or ciprofloxacin [11]. A hospital-based study from 2006 to 2010 in Indonesia also found similar results; S. Typhi showed no resistance against trimethoprim-sulfamethoxazole, ciprofloxacin, and meropenem, 0.9% against ceftriaxone, 1.6% against cefotaxime, and 1.9% against ampicillin [18].…”
Section: Discussionmentioning
confidence: 99%
“…At that time, Paratyphi A was relatively common in North America (12). Today, Paratyphi A accounts for a sizable fraction (14-64%) of all enteric fever in India, Pakistan, Nepal, Indonesia, and China (13)(14)(15)(16), but has largely disappeared from Europe and North America, except for travelers returning from South and Southeast Asia (17,18). Otherwise, little is known about its historical patterns of spread or its evolutionary history.…”
mentioning
confidence: 99%
“…Since 1981 the outbreaks related to salmonellosis had been reported by Cobet et al (1981) who isolated 158 Salmonella Oranienburg from 150 hospitalized patients with diarrhoea. Punjabi et al (2013) reported 296 laboratoryconfirmed enteric fever cases during the 7 months surveillance period in North Jakarta Indonesia, of which 221 (75%) were typhoid fever and 75 (25%) were the paratyphoid fever. Most of the cases occurred among children under five years old.…”
Section: Introductionmentioning
confidence: 99%